Ex Libris Lou Aspereslag / GG. - Gaudaen, Gerard (1927-2003) ([wydawca nieznany], 1967)
Motyl siedzący na otwartej dłoni, u dołu napis: Ex Libris Lou Aspereslag. Sygnatura artysty w obrębie kompozycji.